Occurrence of Saissetia oleae (Olivier) (Hemiptera: Coccidae) in seedlings of Calophyllum brasiliensis Cambess. (Guttiferae) in Diamantina, Minas Gerais, Brazil (Research, Society and Development, 2022)
The objective of this work was to record, for the first time, the occurrence of black scale meal (Saissetia oleae) in seedlings of Landim (Calophyllum brasiliensis) in the municipality of Diamantina, MG, Brazil. Immature and adult mealybugs were observed attacking mainly leaves of C. brasiliensis on the abaxial face. The insects were also present on petioles and stems in primary and secondary growth.